Penggunaan Prototype DC Converter Untuk Peningkatan Kinerja Panel Surya 1000 Watt - Taryana, Taryana; Suprihartini, Yayuk; Soebiantoro, Rubby (Jurnal Ilmiah Global Education, 2024)
Solar power plants (PLTS) are power plants that convert solar energy into environmentally friendly electrical energy. Reducing dependence on fossil fuel electricity and the increasingly expensive price of PLN electricity so that there is a need for alternative sources of renewable electricity, and the obstacle is the large investment in PLTS, including systems on-grid, off-grid, and hybrid. The use of sunlight in solar power plants is still limited to approximately 5 hours, the time range is from 10.00 to 14.30 WIB. To achieve the goal of extending the maximum period for collecting renewable energy, support can be provided by designing a prototype DC Converter, The design to be implemented uses the R&D research method. This research method is carried out to produce a product, test the effectiveness of the product, and perfect the product according to the criteria for creating a new product through different stages. The DC converter prototype functions as a replacement solar Charge Controller (SCC) is low cost and its performance produces electricity from 08:00 to 16:00 WIB. The Inverter is 12V 1000 watts and the output voltage of a 270Wp solar panel is around 33V DC, so the DC conversion function will reduce the output voltage of the solar panel to 12V DC and the load used by 30%. Installed load 240 watts or 0.24 kWh. can be fully lit for an average of 7 hours. By using a DC converter prototype, savings can be achieved assuming the selling price of PLN electricity is Rp. 1,444.70,-/kWH is Rp. 72,812.88/month